Condom use among antiretroviral therapy patients in Ibadan, Nigeria - Joshua O. Akinyemi; Olutosin A. Awolude; Isaac F. Adewole; Phyllis J. Kanki (Journal of Infection in Developing Countries)
Background: While antiretroviral treatment (ART) has improved the health status of people living with HIV, new challenges to their sexual and reproductive health (SRH) needs and their ability to prevent secondary HIV infections have risen. This study aimed to determine the level and factors that affect condom use among ART-experienced patients at the premier teaching hospital in Nigeria.